INSTRUMENTATION DEVELOPMENT FOR RAINFALL INTERCEPTION MEASUREMENT ON A TREE USING WATER BALANCE METHOD - Sensus Wijonarko; Tatik Maftukhah (Instrumentasi, 2014)
A simplified but effective automatic measurement system has been built to give an additional alternative to the more complicated older version apparatus for rainfall interception metering on a representative tree of a subcatchment area. The equipment was installed on Regional Clean Water Company (PDAM) Air Serkuk Sub-Basin, Kubu Watershed, Belitung in 2014. The indirect way, called water balance or weighing method, was used in this study, so that the developed gauge consisted of some gages for gross rainfall, throughfall, stemflow, and canopy area measurements respectively on the selected plantation. Results revealed that the interception was about 11.36%. In other words, for every 100 mm rainfall, there was 11.36 mm interception on trees. Therefore, it was in the range of previous study results conducted by some former researchers in other places.Keywords: Instrumentation, instrument, interception, rainfall, water balance